(untitled) (European Journal of Formal Sciences and Engineering, 2023)
Designing, changing and adapting organizations to secure viability is challenging for companies. Researchers often fail to holistically design or transform organizations. Thus, the aim of this study is to propose a holistic approach how organizations can be designed, changed or managed considering also its implications to production management following lean management principles. Hereby the Viable System Model was applied. This structure can be applied to any kind of structured organization and for its management with goals to be achieved in modern society; however focus of the research is the cluster of manufacturing and assembly companies. Goal of the developed organizational model is to be able to react to all potential company environments by taking decisions regarding organization and production management functions correctly and in the right moment based on the needed information. To ensure this, standardized communication channels were defined. In conclusion this proposed approach enables companies to have internal mechanisms to secure viability and also in production to reduce necessary stocks, lead times, manpower allocation and leads to an increase of the service level to the final customer